Evaluation of the Efficacy and Safety of Antiplatelet Therapeutics in Rabbits. Issue 3 (15th March 2023) - Kuszynski, Dawn S.; Christian, Barbara D.; Bernard, Matthew P.; Lauver, D. Adam
Abstract: Hemostasis is a multifactorial process that involves vasoconstriction of blood vessels, activation of the coagulation cascade, and platelet aggregation. Inappropriate activation of hemostatic processes can result in thrombosis and tissue ischemia. In patients at risk for thrombotic events, antiplatelet therapeutic agents inhibit platelet activation, thereby reducing the incidence of pathologic clot formation. Platelets are activated by several endogenous chemical mediators, including adenosine diphosphate, thrombin, and thromboxane. These activation pathways serve as attractive drug targets. The protocols described in this article are designed to evaluate the preclinical efficacy and safety of novel antiplatelet therapeutics in rabbits. Here, we provide two protocols for blood collection, two for determining platelet activation, and one for assessing bleeding safety. Together, these protocols can be used to characterize the efficacy and safety of antiplatelet agents for hemostasis. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Blood collection via the central ear artery Alternative Protocol 1 : Blood collection via the jugular vein Basic Protocol 2 : Platelet aggregation assessment via light transmission aggregometry Alternative Protocol 2 : Platelet activation assessment via flow cytometry Basic Protocol 3 : Determination of tongue bleeding time